Meschia brevirostris sp. nov., from New Caledonia (Hemiptera: Heteroptera: Lygaeoidea: Meschiidae) - Malipatil, Mallik B.; Masłowski, Adrian; Dobosz, Roland; Taszakowski, Artur (Zootaxa, 2022)
A new species, Meschia brevirostris sp. nov. (Hemiptera: Heteroptera: Lygaeoidea: Meschiidae), is described from New Caledonia. Photographs and SEM micrographs of the male and female habitus, genital structures and selected morphological structures are presented.